2023
DOI: 10.1038/s41598-023-29461-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sentinel surveillance of enteroviruses in Gwangju, South Korea, 2011–2020

Abstract: Human enteroviruses (EVs) are associated with a broad spectrum of diseases. To understand EV epidemiology, we present longitudinal data reflecting changing EV prevalence patterns in South Korea. We collected 7160 specimens from patients with suspected EV infections in ten hospitals in Gwangju, Korea during 2011–2020. RNA extraction and real-time reverse transcription polymerase chain reaction using EV-specific probes and primers were performed. EV genotyping and phylogenetic analysis were performed; EVs were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
0
8
0
2
Order By: Relevance
“…Our laboratory surveillance revealed that this atypical epidemic was primarily caused by CV-A6 infection and no other types of EV could be identified. EV-A71 and CV-A6 caused a major epidemic in 2019 and not EV-A71 but CV-A6 was rarely detected in 2020 [ 24 ]. The degree of sequence similarity in VP1 region at both the nucleotide and amino acid levels was used as a criterion for the identification and assignment of distinct EV subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory surveillance revealed that this atypical epidemic was primarily caused by CV-A6 infection and no other types of EV could be identified. EV-A71 and CV-A6 caused a major epidemic in 2019 and not EV-A71 but CV-A6 was rarely detected in 2020 [ 24 ]. The degree of sequence similarity in VP1 region at both the nucleotide and amino acid levels was used as a criterion for the identification and assignment of distinct EV subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of a single CV-A6 subclade may have been affected by implementation of public health measures to control the SARS-CoV-2 during the pandemic period, which may have led to mitigate the circulation of other EVs. Our surveillance previously reported that nine EV genotypes were identified for the HFMD cases in 2019 [ 24 ]. Among them, the most predominant type was EV-A71, followed by CV-A6, CV-A16, CV-A10, CV-A2, E9, CV-A5, E21, and CV-A9.…”
Section: Discussionmentioning
confidence: 99%
“…Herpangina, like HFMD, is primarily caused by EVs, particularly CVs. Although the majority of herpangina cases have been mostly associated with CVA2, CVA4, CVA6, and CVA10 ( Table 1 ) other CVs types are also responsible for outbreaks/sporadic cases, including CVA1, CVA3, CVA5, CVA7, CVA8, CVA9, CVA12, CVA16, CVA20, CVA22, CVA24, CVB1, CVB2, CVB3, CVB4, CVB5, CVB6 ( Table 1 ) ( Yao et al, 2017 ; Yang et al, 2019 ; Ai et al, 2021 ; Kim et al, 2023 ; Zhao et al, 2020 ; Wenner, 1972 ; Cherry and Krogstad, 2009 ). Additionally, EV coinfection, especially CVs C-species, can favor the emergence of uncommon symptoms ( Zhu et al, 2023 ; Yao et al, 2017 ).…”
Section: Cv-associated Infectionsmentioning
confidence: 99%
“… Associated-diseases Coxsackievirus identified Number of coxsackieviruses types identified Ref. Species A Species B Species C Total HFMD CVA2, CVA4, CVA5, CVA6, CVA7, CVA8, CVA10, CVA12, CVA14, CVA16 CVA9, CVB1-B5 CVA1, CVA11, CVA13, CVA19, CVA20, CVA21, CVA22, CVA24 10 6 8 24 ( Tapparel et al, 2013 ; Sousa et al, 2018 ; Mirand et al, 2012 ; Guan et al, 2015 ; Puenpa et al, 2014 ; Zhu et al, 2023 ; Yao et al, 2017 ; C. Wang et al, 2018 ; Yi et al, 2022 ; Liu et al, 2023 ; Duong et al, 2016 ) Herpangina and other skin manifestations ( CVA2, CVA3, CVA4, CVA5, CVA6, CVA7, CVA8, CVA10, CVA12, CVA16 CVA9, CVB1-B6 CVA1, CVA20, CVA22, CVA24 10 7 4 21 ( Yao et al, 2017 ; Yang et al, 2019 ; Ai et al, 2021 ; Kim et al, 2023 ; Zhao et al, 2020 ; Wenner, 1972 ; Cherry and Krogstad, 2009 ; Cherry, 1982 ) Acute respiratory tract infection CVA2, CVA4, CVA5, CVA6, CVA7, CVA8, CVA10, CVA12, CVA14, CVA16 CVA9, CVB1-B6 CVA21, CVA24 10 7 2 19 ( Xiang et al, 2012 ; Zou et al, 2017 ; Hang et al, 2017 ; B'Krong et al, 2018 ; Jacques et al, 2008 ; Suryadevara et al, 2022 ; Anon., Reports on Isolation/Detection of Viruses, 2005 ) …”
Section: Introductionmentioning
confidence: 99%
“…반면, 우주 감시 레이다는 광학장치보다 낮은 해상도를 가지고 시스템 구 성이 복잡하며 비용이 높지만, 날씨 조건이나 시간에 관 계없이 넓은 범위에서 탐지가 가능하다는 장점이 있다. 국내에서는 우주 감시를 위한 광학 시스템은 구축되어 있지만 레이다 시스템의 개발이 아직 미흡하여 상시 감 시가 가능한 우주 감시 레이다 개발이 필요하다 [2] .…”
unclassified